Stakeholder Analysis dalam Kebijakan Makan Bergizi Gratis di Kabupaten Bangkalan - Lintang Laxita Chandra Dewi; Yusuf Hariyoko; Wahid Hidayat (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Stakeholder Analysis in the implementation of the Free Nutritious Meal (MBG) Policy in Bangkalan Regency is the focus of this study. The MBG program is a national strategy for community nutrition fulfillment inaugurated in 2025 to address stunting prevalence and improve human resource quality. This research uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and documentation in Bangkalan Regency. Using Freeman's (1984) Stakeholder Analysis framework with a power–interest matrix, the study identifies SPPG Kodim 0829 as a key player (Manage Closely), OPD as Keep Informed, DPRD as Keep Satisfied, and beneficiaries as Subjects. Findings show the program has reached 2,345 beneficiaries with positive impacts on nutrition, learning motivation, and household economy. However, four structural challenges exist: risk burden imbalance on SPPG, weak horizontal coordination, absent integrated information systems, and lack of regional regulations formalizing stakeholder roles.